Safety and Tolerability of Initiating Maximum-Dose Sacubitril-Valsartan in Patients on Target Dose Renin-Angiotensin System Inhibitors - Helena Norberg; Ellinor Bergdahl; Krister Lindmark (Cardiovascular Therapeutics)
Aim. Sacubitril-valsartan has proven beneficial in heart failure with reduced ejection fraction. Guidelines recommend initiating half-dose sacubitril-valsartan before up-titration even to patients already on target dose angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARB). To reduce the number of titration steps needed in order to simplify for the patient as well as the clinic, we aimed to investigate the safety and tolerability of switching patients on target dose ACE inhibitors or ARBs directly to maximum-dose sacubitril-valsartan. Methods. This prospective cohort study was conducted between April 2016 and November 2017. A total of 66 patients with heart failure and reduced ejection fraction already on guideline-recommended target dose ACE inhibitors or ARBs (equivalent to enalapril 10 mg twice daily) were switched to maximum-dose sacubitril-valsartan (200 mg twice daily). The patients were followed for twelve months. Results. Patients had a mean age of 72 ± 10 years, mean systolic blood pressure of 121 ± 17 mmHg, and 92% were male. At 12-month follow-up, nine patients (14%) had discontinued sacubitril-valsartan, four patients (6%) had a dose reduction, and 17 patients (26%) had developed symptomatic hypotension. No angioedema occurred within the 12-month follow-up and there were no hospitalizations or emergency room visits within the first 14 days. Conclusions. Switching directly from target dose ACE inhibitors or ARBs to maximum-dose sacubitril-valsartan was safe and generally well tolerated.